Proposta de um guia de boas práticas para a avaliação de impacto ambiental de parques eólicos na zona costeira do Ceará - Preuss, Simone Lima da Costa (2020)
Brazil has good environmental characteristics for the renewable energy sources use, and in recent years, wind farms have grown substantially in Brazil, with a very high number in the Ceara coastal zone. The wind farms installation in the coastal zone have had a negative impact on the abiotic, biotic and anthropic environments. For this reason, the present research had as objective to propose a guide of good practices for the wind farms’ environmental impact assessment in the coastal zone. For this purpose, the research fell into three steps. In the first research part, a document review to establish the context of two study areas: Ceara (CE), Brazil and Western Australia (WA) to determine the coastal zone environmental impacts relevance from wind farm development. In this way, the environmental impact assessment methodologies were carried out, and it was analyzed the environmental impact of wind farms listed in the environmental studies provided by the CE environmental agency, the guides for renewable energy and wind energy in WA, as well as the scientific literature. In the second research part, a survey was carried out with experts in environmental impact assessment and wind energy on these two state jurisdictions: CE and WA, to ask the environmental impacts and the vulnerability of coastal zone relevance regarding the development of wind farms. Finally, in the third part of the research was a review of Australian guides for the development of wind farms. The results obtained showed that the methodologies used in environmental studies, carried out in the licensing process for wind farms in CE have different names, but follow the standard of the checklist methodology. The wind farms’ negative environmental impacts analyzed, and the results obtained through the experts' responses contributed to the coastal zone environmental impact relevance assessment, which may imply significant changes in its natural characteristics. The results suggest that the environmental factors assessed by specialists with minor, moderate and high relevance to the coastal zone vulnerability due to the installation and operation of wind farms must be in the Term of Reference (TR) requested by the CE environmental agency. In addition, WA wind farm guides can be useful in the CE and Brazil context in order to guide a good practice guide for wind farms in the coastal zone. In this way, the good practice guide can orient that the Environmental Impact Studies and the Environmental Impact Reports (EIA / RIMA) must be requested by the CE environmental agency for wind projects that, regardless of size, have their installation and operation proposed in the CE coastal zone. The guidance for requesting the EIA / RIMA is mainly because the EIA demands primary data for the environmental impact assessments.